Back on the campaign of solidarity with the victims of portete bay: An ethnographic study of transnational activism (2006-2007) (2012)
Based on authors of French critical sociology, this article intends to analyze the way in which an 'indigenous cause' builds up and transnationally mobilizes through porous borders among different levels of action. To this end, this article presents a case study: The International Solidarity Campaign, in Australia, with the Victims of Pórtete Bay (2004). This work, on a micro level, intends to contribute, from the analysis of unpublished ethnographic materials and the reconstruction of paths, to understanding the working logics of these networks, incorporating new elements of reflection on the theories of transnational activism.